A review of methods to study hydration effects on cartilage friction. (2nd October 2017) - Moore, Axel C.; Schrader, Jordyn Lee; Ulvila, Jaclyn J.; Burris, David L.
Abstract: The mechanical and tribological responses of cartilage depend strongly on its hydration state, which is a function of the mechanical and tribological conditions of the contact. The interdependencies between stresses and water content make controlled studies of cartilage function difficult. This paper reviews some of the experimental challenges in cartilage tribology and the methods we have used to help address them. For example, we demonstrate a simple method to eliminate the frictional errors associated with sample curvature in the migrating contact area and show how in situ measurements can be used to assess hydration and its effect on friction. Finally, we demonstrate a new explant testing configuration, the convergent stationary contact area (cSCA), in which cartilage loses, maintains and recovers interstitial water in response to loading and sliding in a manner consistent with in vivo joint mechanics. We propose that the cSCA provides an ideal test bed for studying cartilage tribology, while maximising experimental control and physiological relevance.